Doping modification, defects construction, and surface engineering: Design of cost-effective high-performance electrocatalysts and their application in alkaline seawater splitting. (September 2021) - Wang, Xiao Hu; Ling, Yu; Wu, Bin; Li, Bang Lin; Li, Xiao Lin; Lei, Jing Lei; Li, Nian Bing; Luo, Hong Qun
Abstract: The shortage of pure-water and high-energy consumption of low-grade water treatments force the development of direct seawater-electrolysis. Herein, experiments and calculations reveal the redistribution of electron density due to doping and vacancy defects, and confirm the contribution of multiple active sites to the dissociation and desorption of water with favorable thermodynamics. The Co/Ni-doped defect-rich Cu-based oxides (CNC-MO) nanoarrays promote water dissociation and hydrogen desorption via bonding with *OH and *H respectively, thus accelerating hydrogen evolution reaction (HER). The Ni/Co-doped defect-rich Cu-based sulfides (CNC-MS) nanorods modulate the adsorption state of *OH while effectively adsorbing and isolating *H to improve the oxygen evolution reaction (OER) kinetics. Asymmetric electrodes can achieve alkaline seawater electrolysis with 100 mA cm −2 at a voltage of 1.61 V. The corrosion resistance, high efficiency, and selectivity of electrodes can remain stable for 1200 h in a saline-alkali medium, and then gradually decline with sites blocking and deep corrosion. The aim of this work is to propose design strategies for the construction of high-performance electrocatalysts for seawater splitting while balancing multiple factors such as cost, efficiency, and durability. Graphical Abstract: ga1 Highlights: ● CuOx containing OVs and doped Ni/Co as dual sites accelerate H2 O dissociation and H desorption to improve HER activity. ● CuSx accelerates proton-electron transfer, while SVs with Ni kinetically lower the energy barrier of OER intermediates. ● Active surface textures constructed by alloying and anodization greatly improve the catalytic active area of electrodes. ● Hierarchical layers composed of internal oxides and surface sulfides exhibit good resistance to COR and halide attack. ● Overall seawater splitting can be steady performed at 1.61 V with 100 mA cm −2 for more than 1200 h.